2008
DOI: 10.1063/1.2973682
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of core and valence binding energies in Pd nanoparticles: Interplay of quantum confinement and coordination reduction

Abstract: An analysis is given of the electronic structure of Pd nanoparticles synthesized by inert gas evaporation technique. A study of the effect of size on various core and valence electrons in Pd nanoparticles reveals a varied dependence of binding energy of electrons in different electronic levels. The shift in the Pd x-ray photoelectron spectroscopy 4d valence band centroid is more than the core level shift. The results of the present study provide a direct evidence of interplay of quantum confinement ͑a size eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
88
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 16 publications
6
88
1
Order By: Relevance
“…A similar LC has been reported in Pd metal nanoparticles with decrease in size. 4 This observed XRD shift has been attributed to surface bond contraction with coordination number reduction and enhanced surface area at lower particle size. 4 In case of Pd-Cu nanoparticles, ͑111͒ peak is observed to lie between the peaks of Pd and Cu nanoparticles ͑of same size͒, which confirms the Pd-Cu alloy formation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…A similar LC has been reported in Pd metal nanoparticles with decrease in size. 4 This observed XRD shift has been attributed to surface bond contraction with coordination number reduction and enhanced surface area at lower particle size. 4 In case of Pd-Cu nanoparticles, ͑111͒ peak is observed to lie between the peaks of Pd and Cu nanoparticles ͑of same size͒, which confirms the Pd-Cu alloy formation.…”
mentioning
confidence: 99%
“…4 This observed XRD shift has been attributed to surface bond contraction with coordination number reduction and enhanced surface area at lower particle size. 4 In case of Pd-Cu nanoparticles, ͑111͒ peak is observed to lie between the peaks of Pd and Cu nanoparticles ͑of same size͒, which confirms the Pd-Cu alloy formation. Energy dispersive x-ray analysis ͑EDX͒ studies carried out on Pd-Cu3.5 sample sintered at different temperatures ranging from 300 to 900°C has confirmed that the average atomic composition during compaction is 65:35 ͑Pd:Cu͒ and remains unchanged and thus the change in the XRD peak positions is not due to any composition change.…”
mentioning
confidence: 99%
See 3 more Smart Citations